2013
DOI: 10.1182/blood-2013-05-505511
|View full text |Cite
|
Sign up to set email alerts
|

Genetic sequence analysis of inherited bleeding diseases

Abstract: The genes encoding the coagulation factor proteins were among the first human genes to be characterized over 25 years ago. Since then, significant progress has been made in the translational application of this information for the 2 commonest severe inherited bleeding disorders, hemophilia A and B. For these X-linked disorders, genetic characterization of the disease-causing mutations is now incorporated into the standard of care and genetic information is used for risk stratification of treatment complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 94 publications
0
35
0
4
Order By: Relevance
“…1 Inheritance pattern is autosomal recessive for all RBDs, except for some cases of FXI and of hypo-and dysfibrinogenemia. Information on RBD identified mutations is available through the International Society on 29 Insertion/deletion mutations represent 20% to 30% of gene variations of the fibrinogen, FV, MCFD2, and FXIII genes and ,15% of remaining coagulation factor mutations. Splicing and nonsense mutations comprise 5% to 15% of coagulation factor-identified mutations, with a maximum rate of 20% in the LMAN1 gene.…”
Section: Molecular Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…1 Inheritance pattern is autosomal recessive for all RBDs, except for some cases of FXI and of hypo-and dysfibrinogenemia. Information on RBD identified mutations is available through the International Society on 29 Insertion/deletion mutations represent 20% to 30% of gene variations of the fibrinogen, FV, MCFD2, and FXIII genes and ,15% of remaining coagulation factor mutations. Splicing and nonsense mutations comprise 5% to 15% of coagulation factor-identified mutations, with a maximum rate of 20% in the LMAN1 gene.…”
Section: Molecular Diagnosismentioning
confidence: 99%
“…Splicing and nonsense mutations comprise 5% to 15% of coagulation factor-identified mutations, with a maximum rate of 20% in the LMAN1 gene. 29 Variants located in the 39 and 59 untranslated regions of the genes are least frequent (,5%) and found only in fibrinogen, FVII, FXI, and FXIII. 29 Despite significant advances in knowledge, 5% to 10% of affected patients with severe deficiencies have no identifiable genetic defect; here the use of next-generation sequencing, correlated with additional investigation on the deleterious/causative role of identified sequence variations, may elucidate novel genetic pathways.…”
Section: Molecular Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…The second most frequent mutation has been observed in intron 1 as an inversion with a prevalence of about 1-5% among haemophilia-A patients [5,6]. A total of 1388 missense/ nonsense, 377 small deletions, 156 splicing, 117 small insertions, 27 small indels, 213 gross deletions, 26 gross insertions, 12 complex rearrangements, and four regulatory mutations have so far been detected [3,7]. Several studies have been conducted describing the mutations in the Western populations [8][9][10][11][12], however, the spectrum and nature of common mutations carrying haemophilia A in Arab population is still lacking investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The first review, "Genetic sequence analysis of inherited bleeding diseases," was written by Dr Flora Peyvandi, Dr Tom Kunicki, and Dr David Lillicrap from the University of Milan, Italy; the Children's Hospital of Orange County (Orange, CA); and Queen's University in Kingston, ON, Canada, respectively. 7 This review focuses on bleeding disorders and begins with a description of the enormous variation found in databases of mutations associated with hemophilia A and hemophilia B. The review goes on to describe targeted sequencing of clotting factor genes before culminating in a review of how whole-genome analysis has identified new mutations that cause bleeding disorders.…”
mentioning
confidence: 99%